The role and clinical value of EUS in a multimodality esophageal carcinoma staging program with CT and positron emission tomography - Pfau, Patrick R.; Perlman, Scott B.; Stanko, Peter; Frick, Terrence J.; Gopal, Deepak V.; Said, Adnan; Zhang, Zhengjun; Weigel, Tracey (Gastrointestinal endoscopy, 2007)
EUS, CT, and positron emission tomography (PET) have all been used in the preoperative staging of esophageal cancer separately or in various combinations. Our purpose was to determine the value and role of EUS when used in conjunction with CT and PET imaging in staging cancer of the esophagus and gastroesophageal junction. Retrospective single-center clinical trial. Academic tertiary care center. Data were examined for 56 patients who concomitantly underwent examination with EUS, CT, and PET in a multimodality staging program. EUS, CT, and PET were examined for their ability to detect the primary tumor, local tumor stage, locoregional adenopathy, and distant metastases. With use of surgical resection as baseline therapy, the frequency at which EUS, CT, and PET affected and changed management was examined. EUS is the only imaging test that identified all primary tumors and provided tumor staging. EUS identified a significantly greater number of patients (58.9%) with locoregional nodes than did CT (26.8%), P = .0006, or PET (37.5%), P = .02. CT identified 14.3% and PET identified 26.8% of patients with distant metastases. With CT alone, 15.2% of patients were not taken to surgery, whereas PET affected management by preventing surgery because of metastatic disease in 28.3% of patients. EUS changed management by guiding the need for neoadjuvant therapy in 34.8% of patients. Retrospective study, nonblinded study, lack of pathologic reference standard. The primary strength of EUS in a multimodality staging strategy is in identifying patients with locally advanced disease and guiding the need for preoperative neoadjuvant therapy. EUS is not suited to determine resectability of esophageal cancer alone and thus is most effective when used in conjunction with other imaging tests such as CT and PET.